All-Optical Clocked D Flip-Flop Memory Using A Hybrid Integrated S-R Latch - Reis, Cláudia
We demonstrate, by using multiple Mach-Zehnder interferometer (MZI)-semiconductor optical amplifier structures, an all-optical synchronous D type flip-flop, with high-photonic integration capability. Experimental performance analysis shows its functional and performance feasibility and high-switching speeds were achieved. (C) 2011 Wiley Periodicals, Inc. Microwave Opt Technol Lett 53:1201-1204, 2011; View this article online at wileyonlinelibrary.com. DOI 10.1002/mop.25998